Effect of Vitamin C Bioencapsulation in Natural Feed on Protein, Fat, Energy, and Mortality of Milkfish Larvae (Chanos chanos) - Sri Mulyani; Sutia Budi; Indra Cahyono; Khairiman Khairiman (Jurnal Kelautan Tropis, 2023)
Indications of milkfish larvae problems show lack symptoms of vitamin C in the tissues, which will cause defective bone formation and become an inhibitor factor in growth and mortality. This research aims to investigate the influence of vitamin C bioencapsulation on rotifer and artemia in protein retention, fat, energy, and the cause of death in milkfish larvae (Chanos chanos). The dose of vitamin C used in this study were 0 (control), 50, 100, 150, and 200 mg L-1. The treatment starts from D-1 to D-30 stadia of milkfish larvae, with 30-day maintenance. The density of milkfish larvae utilized is 20 L-1. The protein and fat content of milkfish larvae bodies were measured using a proximate analysis, and the energy content of the feed was measured using a bomb calorimeter. Mortality was observed under the Ministry of Health of Republic Indonesia standard binocular microscope by identifying larvae that died daily in each container. This research shows that vitamin C bioencapsulation in rotifer and artemia affects the retention rate of protein, fat, energy and the cause of milkfish larvae mortality. The dose of vitamin C of 150 and 200 mg L-1 is effective in improving protein, fat, and energy retention, which can minimize the cause of milkfish larvae mortality. The best results are obtained by bioencapsulating Vitamin C on rotifer and artemia with dose of 150 mg L-1.